Analisis Pengaruh Indeks Pembangunan Manusia Dan Tenaga Kerja Terhadap Kemiskinan Di Provinsi Sumatera Utara - Taufik Hidayat (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Poverty continues to be a major problem in the world, especially in North Sumatra Province. This study aims to examine and analyze the Effect of the Human Development Index and Workforce on Poverty in North Sumatra Province in 2015-2020. This type of data uses secondary data obtained from BPS North Sumatra and also journals as research support. The analysis used in this study is a quantitative method and uses eviews 9. In this model the independent variables used are the Human Development Index and Labor. While the dependent variable is Poverty. The regression results show that the Correlation Coefficient (R) is obtained with a multiple correlation of R=0.53 or 53%, so it can be concluded that there is a strong correlation between the HDI and Workforce variables on Poverty in North Sumatra Province. The coefficient of determination (R2) from the calculation of the coefficient of determination (R2) is 0.06 or 6%, meaning that 6% of poverty in North Sumatra Province is influenced by HDI and Labor. While 94% is influenced by other variables not examined.